The Role of Product Life Cycle Balancing in Reducing Costs: Iraqi’s experience - Wahhab, Asaad Mohammed Ali; Zaid, Zahraa Yahya Abd; Jaafar, Zahraa Ali (Technium Social Sciences Journal, 2022)
The current research aims to present a cognitive discussion of one of the modern strategic techniques in the field of cost and management accounting, which is represented by the product life cycle balancing technique, and to indicate the role it plays in terms of reducing the costs of laboratory products, the research sample, mainly if time is used as a cost vector in its application, with Maintaining its quality, as well as assisting the administration in making various decisions by calculating the cost more accurately than traditional methods. The General Company for Electrical and Electronic Industries in Baghdad was chosen to achieve this goal. One of its laboratories was represented by the air-cooled engine production plant in Al-Waziriya as a sample. For the research, the researcher relied when applying this technique on data and information obtained from the laboratory records of the research sample, as well as visits and field coexistence of researchers in the above laboratory, interviewing officials and individuals working in it, with a view of cost reports, accounting records, and time cards related to The lab, to apply the above technique. The research concluded that the air-cooled engine production plant suffers from the absence of any features of the application of modern strategic techniques that are concerned with reducing costs, the most important of which is the product life cycle technology and preparing the budget in its shadow and by using time as a cost vector through which the costs of the laboratory products can be reduced, the research sample, as well as On the lack of a clear role for the activity of the research and development department, to follow up the changes and developments witnessed by the contemporary business environment, in which the laboratory has become directed by the customer, in addition to the fact that the use of modern technologies in the field of cost and management accounting would contribute to keeping pace with progress, development and growth in the industrial and commercial reality. The country’s economy,